Design Of Up-Conversion Mixer Front End Transmitter For Cdma Application At 900mhz Using Cmos Technology - Tan, Wee Chuan (Universiti Sains Malaysia, 2005)
This report included design, and simulation results of up conversion mixer that operate at LO frequency 798 MHz. System and circuit design had been carried out with the aid of software program Cadence. Two steps up conversion mixer is a type of mixer that combines a single side band mixer and a double side balanced mixer to perform two steps up conversion process. First part of mixer will convert IF input signal at 40 MHz to 572 MHz by multiplication with LO signal at 532 MHz. The output of mixer part one consists 2 spectrum frequency at 572 MHz and 492 MHz. A Band pass filter is needed to filter the spectrum on 492MHz, the output signal after filtering process by band pass filter is at 572MHz. The output signal will become the input signal for mixer second part. Second part of mixer will convert the input signal at 572MHz to 838MHz by multiplication with another LO signal at 266MHz. The detail circuits design is discussed in chapter 5 and performance for each part of the mixer system are tested and measured in cadence. The results are listed in Chapter 6.